Project Leadership and Quality Performance of Construction Projects (International Journal of Built Environment and Sustainability, 2017)
Background: The construction industry in Nigeria, is pigeonholed by poor quality of construction products as a result of the inherent corruption in the country. Lack of purposeful leadership and inappropriate choice of leadership styles in the industry have been attributed to project failure. Abandoned and failed projects are more predominant in the public sector which litters every corner of the country. Objectives: The objective of this paper is to assess the impact of leadership styles on quality performance criteria of public projects in Nigeria. Methodology: A total of 43 questionnaires were distributed to 3 key groups of respondents (Quantity Surveyors, Builders, and Architects) who are project managers in Nigeria. Descriptive and Inferential statistics were used to analyse the data using the Statistical Package for Social Sciences (SPSS). Likert Scale was used to measure the independent variables (leadership style): facilitative, coaching, delegating and directing; and the level of achievement of projects based on the dependent variables (quality and function performance criteria) which are: achieving highest aesthetic quality; and functional building that fits its purpose. Findings: The study revealed that Directing is the major leadership style used by project managers in Nigeria. Amongst the leadership styles which has the most impact on quality performance indicators is also directing which has the most relative influence on achieving highest aesthetic quality and functional building that fits its purpose. Conclusion/Recommendation/Way forward: The underlying relationship between Directing leadership styles and the performance criteria of achieving highest aesthetic quality and functional building that fits its purpose will be beneficial to the Nigerian construction environment.